Fab-dimerized glycan-reactive antibodies are a structural category of natural antibodies - Williams, Wilton B; Meyerhoff, R Ryan; Edwards, R J; Li, Hui; Manne, Kartik; Nicely, Nathan I; Henderson, Rory; Zhou, Ye; Janowska, Katarzyna; Mansouri, Katayoun; Gobeil, Sophie; Evangelous, Tyler; et al. (Cell, 2021)
Natural antibodies (Abs) can target host glycans on the surface of pathogens. We studied the evolution of glycan-reactive B cells of rhesus macaques and humans using glycosylated HIV-1 envelope (Env) as a model antigen. 2G12 is a broadly neutralizing Ab (bnAb) that targets a conserved glycan patch on Env of geographically diverse HIV-1 strains using a unique heavy-chain (V ) domain-swapped architecture that results in fragment antigen-binding (Fab) dimerization. Here, we describe HIV-1 Env Fab-dimerized glycan (FDG)-reactive bnAbs without V -swapped domains from simian-human immunodeficiency virus (SHIV)-infected macaques. FDG Abs also recognized cell-surface glycans on diverse pathogens, including yeast and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike. FDG precursors were expanded by glycan-bearing immunogens in macaques and were abundant in HIV-1-naive humans. Moreover, FDG precursors were predominately mutated IgM IgD CD27 , thus suggesting that they originated from a pool of antigen-experienced IgM or marginal zone B cells.